Partial and combined partial knee arthroplasty: greater anterior-posterior stability than posterior-cruciate retaining total knee arthroplasty - Garner,A; Dandridge,O; Amis,A; Cobb,J; van,Arkel R (The Journal of Arthroplasty, 2021)
BackgroundLittle is known regarding anterior-posterior stability after anterior cruciate ligament–preserving partial (PKA) and combined partial knee arthroplasty (CPKA) compared to standard posterior cruciate–retaining total knee arthroplasty (TKA).MethodsThe anterior-posterior tibial translation of twenty-four cadaveric knees was measured, with optical tracking, while under 90N drawer with the knee flexed 0-90°. Knees were tested before and after PKA, CPKA (medial and lateral bicompartmental and bi-unicondylar), and then posterior cruciate–retaining TKA. The anterior-posterior tibial translations of the arthroplasty states, at each flexion angle, were compared to the native knee and each other with repeated measures analyses of variance and post-hoc t-tests.ResultsUnicompartmental and bicompartmental arthroplasty states had similar laxities to the native knee and to each other, with ≤1-mm differences throughout the flexion range (P ≥ .199). Bi-unicondylar arthroplasty resulted in 6- to 8-mm increase of anterior tibial translation at high flexion angles compared to the native knee (P ≤ .023 at 80-90°). Meanwhile, TKA exhibited increased laxity across all flexion angles, with increased anterior tibial translation of up to 18 ± 6 mm (P < .001) and increased posterior translation of up to 4 ± 2 mm (P < .001).ConclusionsIn a cadaveric study, anterior-posterior tibial translation did not differ from native laxity after PKA and CPKA. Posterior cruciate ligament–preserving TKA demonstrated increased laxity, particularly in anterior tibial translation.